What is eSports and why do people watch it?. Issue 2 (3rd April 2017) - Hamari, Juho; Sjöblom, Max
Abstract : Purpose: The purpose of this paper is to investigate why do people spectate eSports on the internet. The authors define eSports (electronic sports) as "a form of sports where the primary aspects of the sport are facilitated by electronic systems; the input of players and teams as well as the output of the eSports system are mediated by human-computer interfaces." In more practical terms, eSports refer to competitive video gaming (broadcasted on the internet). Design/methodology/approach: The study employs the motivations scale for sports consumption which is one of the most widely applied measurement instruments for sports consumption in general. The questionnaire was designed and pre-tested before distributing to target respondents ( n =888). The reliability and validity of the instrument both met the commonly accepted guidelines. The model was assessed first by examining its measurement model and then the structural model. Findings: The results indicate that escapism, acquiring knowledge about the games being played, novelty and eSports athlete aggressiveness were found to positively predict eSport spectating frequency. Originality/value: During recent years, eSports (electronic sports) and video game streaming have become rapidly growing forms of new media in the internet driven by the growing provenance of (online) games and online broadcasting technologies. Today, hundreds of millions of people spectate eSports. The present investigation presents a large study on gratification-related determinants of why people spectate eSports on the internet. Moreover, the study proposes a definition for eSports and further discusses how eSports can be seen as a form of sports.